Daily non‐invasive haemodynamic telemonitoring for efficacy evaluation of MitraClip® implantation in patients with advanced systolic heart failure. (12th June 2018) - Herrmann, Ester; Ecke, Andreas; Herrmann, Eva; Eissing, Nina; Fichtlscherer, Stephan; Zeiher, Andreas M.; Assmus, Birgit
Abstract: Aim: Patients with advanced systolic chronic heart failure frequently suffer from progressive functional mitral regurgitation. We report our initial experience in patients with an implanted pulmonary artery pressure (PAP) sensor, who developed severe mitral regurgitation, which was treated with the MitraClip system. We non‐invasively compared changes in PAP values in patients after MitraClip with PAP changes in patients without MitraClip. Methods and results: Among 28 patients with New York Heart Association III heart failure with implanted PAP sensor for haemodynamic telemonitoring from a single centre, four patients (age 66 ± 6 years, left ventricular ejection fraction 21 ± 3%, and cardiac index 1.8 ± 0.3) received a MitraClip procedure and were compared with 24 patients (age 72 ± 8 years, left ventricular ejection fraction 26 ± 9.9%, and cardiac index 2.0 ± 1.0) without MitraClip procedure in a descriptive manner. Ambulatory PAP values were followed for 90 days in both groups. In comparison with the PAP values 4 weeks before MitraClip procedure, PAP was profoundly reduced in all four patients after 30 days (ΔPAPmean −11 ± 5, ΔPAPdiast −7 ± 3 mmHg, P < 0.02) as well as after 90 days (ΔPAPmean −6.3 ± 6, ΔPAPdiast −1 ± 3 mmHg). Reductions in PAP were accompanied by a profound reduction in N terminal pro brain natriuretic peptide as well as clinical and echocardiographic improvement. When analysing the dynamics with a regression model, reductions in all PAP values were significantly greater after MitraClip compared with conservative haemodynamic monitoring ( P < 0.001). Conclusions: The efficacy of the interventional MitraClip procedure on clinical symptoms can be confirmed by haemodynamic telemonitoring. Thus, daily non‐invasive haemodynamic telemonitoring allows, for the first time, for a continuous assessment of the haemodynamic efficacy of novel therapies in patients with chronic heart failure.